On a zero-mass (N, q)-Laplacian equation in RN with exponential critical growth. (December 2021) - Carvalho, J.L.; Figueiredo, G.M.; Furtado, M.F.; Medeiros, E.
Abstract: In this work, we investigate the existence of solution for the quasilinear elliptic equation − Δ N u − Δ q u = f ( u ) in R N, where 1 < q < N and the nonlinearity f has exponential critical growth in the Trudinger–Moser sense. In order to obtain the solution, we use a variational approach based on a new Trudinger–Moser type inequality which is proved here.